Serum neopterin, YKL-40, IL-6, and TNF-α in patients with obstructive sleep apnea - Admış, Özlem; Şahin, İbrahim Ethem; Balbay, Ege Güleç; Cangur, Şengül (Acta Medica, 2023)
Objective: Obstructive Sleep Apnea (OSA) is characterized by recurrent episodes of complete or partial upper airway obstruction during sleep. The role of locally increased inflammation in the upper respiratory tract is known in the pathogenesis of OSA. This study aimed to examine the role of some inflammatory markers in OSA. Materials and Methods: Adult patients who underwent diagnostic polysomnography (PSG) for the first time, were evaluated in this prospective study. Serum levels of neopterin, human cartilage glycoprotein 39 (YKL-40), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were examined in the study group. Results: The study included 165 adult patients. Individuals of 56 who were did not have OSA were taken as the control group. Patients diagnosed with OSA (n=109) were included in the study and divided into two groups mild-moderate and severe based on the OSA apnea-hypopnea index (AHI). The study groups were divided into 3 cathegories: AHI <5 (control) Group 1, AHI 5-15 (mild), and AHI 15-30 (moderate) Group 2, AHI>30 (severe) Group 3. Individuals of 165 who completed the study [Group 1 (n=56), Group 2 (n=69), Group 3 (n=40)] were included in the statistical evaluation. There was a significant difference between the groups in terms of neopterin, YKL-40, and IL-6 values (p<0.05). The median value of IL-6 and neopterin measured in the severe group was significantly higher than the value measured in the control and mild-moderate groups (p<0.001). The mean value of YKL-40 measured in the severe group was significantly higher than the value measured in the control group (p=0.012). No significant difference was observed in TNF-α serum levels of groups. Conclusion: Serum levels of neopterin, YKL-40, and IL-6 were found to be elevated in OSA patients (especially in the severe group).